2019
DOI: 10.1177/0363546518823556
|View full text |Cite
|
Sign up to set email alerts
|

Anatomic Features of the Tibial Plateau Predict Outcomes of ACL Reconstruction Within 7 Years After Surgery

Abstract: Background: Multiple anatomical features of the femoral condyles and tibial plateau have been shown to influence knee biomechanics and risk of anterior cruciate ligament (ACL) injury. However, it remains unclear how these anatomical factors affect the midterm outcomes of ACL reconstruction. Hypothesis: Decreased femoral notch width, increased posterior and coronal slopes, and decreased concavity of the tibial plateau are associated with inferior clinical, patient-reported and osteoarthritis-related outcomes 7 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
30
0
2

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 27 publications
(33 citation statements)
references
References 49 publications
1
30
0
2
Order By: Relevance
“…While there is limited information about the effect of posterolateral tibial plateau impaction fractures on outcomes after ACL reconstruction (ACLR), previous studies have evaluated the effect of altered osseous geometry of the lateral tibial plateau on knee biomechanics. 17,24,32 A decreased medial-to-lateral distance of the lateral tibial plateau has been reported to be associated with a high-grade pivot shift, 24 and the lateral tibial plateau’s anterior-to-posterior articular depth measured on magnetic resonance imaging (MRI) has been reported to be decreased in patients with ACL tears compared with controls. 34 Furthermore, higher amounts of anterior subluxation of the lateral tibial plateau measured on MRI in patients with ACL tears have been associated with a higher grade pivot shift.…”
mentioning
confidence: 99%
“…While there is limited information about the effect of posterolateral tibial plateau impaction fractures on outcomes after ACL reconstruction (ACLR), previous studies have evaluated the effect of altered osseous geometry of the lateral tibial plateau on knee biomechanics. 17,24,32 A decreased medial-to-lateral distance of the lateral tibial plateau has been reported to be associated with a high-grade pivot shift, 24 and the lateral tibial plateau’s anterior-to-posterior articular depth measured on magnetic resonance imaging (MRI) has been reported to be decreased in patients with ACL tears compared with controls. 34 Furthermore, higher amounts of anterior subluxation of the lateral tibial plateau measured on MRI in patients with ACL tears have been associated with a higher grade pivot shift.…”
mentioning
confidence: 99%
“…Correction of varus deformity is an important factor for the success of the procedure. 8 , 9 Combinate varus high tibial osteotomy and ACL-reconstruction procedures show significant improvement in postoperative functional outcomes and low rates of complications, re-ruptures or revision surgery. 10 , 11 The target is a slight overcorrected alignment with 1° to 3° of valgus.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies have also established links between some of these anatomic features and an increased risk of secondary ACL injuries 6,24,25,32,41 as well as inferior outcomes after ACL reconstruction. 19 Some of these anatomic features have also been reported to be different in male versus female patients, with female patients having a higher-risk anatomic profile. 36 In addition, a few studies have also shown age-related changes in a subset of these anatomic features, including decreases in the lateral tibial slope and increases in the notch width by age.…”
mentioning
confidence: 99%